Enhancing Integrated Care Through the Voluntary and Community Sector: A Lean Management and Dynamic Capabilities Perspective - Huay Ling Tay (International Journal of Integrated Care)
The Voluntary and Community Sector (VCS) is a critical contributor to integrated care, bridging gaps between health and social care services. However, operational inefficiencies and challenges in adapting to dynamic care environments hinder its full potential. This paper clarifies the perspective—drawn from research and practice—on applying Lean Management principles and Dynamic Capabilities Theory to enhance VCS operations. Using practical vignettes, it illustrates how these frameworks can improve volunteer recruitment, retention, and resource allocation, fostering efficiency and adaptability. Recommendations focus on specific aspects of integrated care, including service coordination, crisis adaptability, and volunteer management, leading to better patient outcomes.